Discovery of 3-(4-sulfamoylnaphthyl)pyrazolo[1, 5-a]pyrimidines as potent and selective ALK2 inhibitors. Issue 20 (1st November 2018) - Jiang, Jian-kang; Huang, Xiuli; Shamim, Khalida; Patel, Paresma R.; Lee, Arthur; Wang, Amy Q.; Nguyen, Kimloan; Tawa, Gregory; Cuny, Gregory D.; Yu, Paul B.; Zheng, Wei; Xu, Xin; et al.
Graphical abstract: Highlights: Identification of a novel class of 4-sulfamoylnaphthyl series ALK2 inhibitor. Excellent selectivity for ALK2 over ALK3 with additional overall kinome selectivity. Key distinctive features identified in the ALK3 homology model to explain ALK2 vs ALK3 selectivity. Abstract: The pyrazolo[1, 5- a ]pyrimidine LDN-193189 is a potent inhibitor of activin receptor-like kinase 2 (ALK2) but is nonselective for highly homologous ALK3 and shows only modest kinome selectivity. Herein, we describe the discovery of a novel series of potent and selective ALK2 inhibitors by replacing the quinolinyl with a 4-(sulfamoyl)naphthyl, yielding ALK2 inhibitors that exhibit not only excellent discrimination versus ALK3 but also high kinome selectivity. In addition, the optimized compound23 demonstrates good ADME and in vivo pharmacokinetic properties.